"Rockin' All Over The World": organisational improvisation lessons from the music-based practitioner. (2015) - Leybourne, Stephen A.; Cook, Peter
This paper explores the relationships and interactions between organisational improvisational activity and differing modes of improvisational expertise utilised by musicians from a range of musical genres. The evolving literature on organisational improvisation has been considered, together with parallel or reinforcing lessons drawn from the orchestral, jazz, and rock musical genres. It is evident that when we consider leadership and management, that more flexible and less rigid structures are being considered in a world of networked organisational structures. Successful managers and leaders draw on improvisational decisions and interventions that are grounded in experience and prior knowledge. Indeed, a degree of creative or constructive deviance is shown to be useful in achieving in the progressive modern organisation. Improvisational organisations have to be specially competent in the management of the unknown and unknowable rather than becoming blocked by such circumstances, and this paper draws out a number of lessons from a range of musical and organisational sources can assist the management practitioner.